Aristolochic acid induces acute kidney injury through ferroptosis - Huang, Xuan; Liu, Ruihua; Zhan, Cuixia; Wu, Haishan; Fan, Jinjin; Li, Zhijian; Yang, Xiao (Frontiers in Pharmacology, 2024)
Aristolochic acid (AA)-induced acute kidney injury (AKI) presents with progressive decline in renal function and rapid progression to end-stage renal disease. Among the multiple mechanisms identified in AKI, ferroptosis has been shown to be involved in various forms of AKI. But few studies have elucidated the role of ferroptosis in AA-induced AKI. In this study, we investigated the role of ferroptosis in AA-induced acute renal tubular injury in vivo and in vitro. Mice with acute aristolochic acid nephropathy showed increased malondialdehyde levels, aggravated lipid peroxidation, decreased superoxide dismutase activity, and glutathione depletion. The expression of glutathione peroxidase 4 was decreased and the expression of acyl-CoA synthetase long-chain family member 4 was increased. Inhibition of ferroptosis by ferrostatin-1 significantly improved the renal function, reduced histopathological lesions, partially alleviated lipid peroxidation, and restored the antioxidant capacity. In vitro studies also revealed that AA significantly reduced cell viability, induced reactive oxygen species production, increased intracellular iron level and decreased ferroptosis-related protein expression. Inhibition of ferroptosis significantly increased cell viability and attenuated AA-induced renal tubular epithelial cell injury. It is suggested that ferroptosis plays an important role in AAinduced acute tubular injury. And inhibition of ferroptosis may exert renoprotective effects possibly by preventing lipid peroxidation, restoring the antioxidant activity or regulating iron metabolism.